Improving chronic myeloid leukemia management and quality of life: patient and physician survey on unmet needs from the CML SUN survey - Fabian Lang; Zack Pemberton-Whiteley; Joannie Clements; Cristina Ruiz; Delphine Rea; Lisa Machado; Naoto Takahashi; Sung-Ho Moon; Andrew Grigg; Cornelia Borowczak; Peter Schuld; Pauline Frank; et al. (Haematologica, 2025)
For patients with chronic myeloid leukemia in chronic phase (CML-CP), disease management, treatment experiences, and decisions around switching therapies due to resistance or intolerance can have significant impacts on their lives. Experiences and perspectives regarding the roles of patients and treating physicians in shared decision-making are poorly understood. The CML Survey on Unmet Needs (CML SUN), the largest CML survey to date, was initiated to gather insights from patients with CML-CP and physicians on disease management, including treatment goals, decision-making, satisfaction, tolerability and the impact of CML on daily life. The survey was deployed in 11 countries with 361 patient and 198 physician participants and comprised separate questionnaires for each group. Results indicated that nearly three-quarters of physicians saw themselves as the ultimate initial treatment decision-makers; only a quarter of patients reported that these decisions were discussed and decided together with their physician. Nearly half of physicians reported making treatment decisions across all lines of therapy with little to no input from the patient. Disparities between patient and physician opinions were observed regarding treatment goals, especially the balance between efficacy and tolerability. The CML SUN highlights the need for improvements in communication about treatment options and the importance of shared treatment decisionmaking to unify treatment goals.